Diversity of viral communities in faecal samples of farmed red foxes. Issue 1 (January 2023) - Zhang, Dianqi; Wang, Yan; Chen, Xu; He, Yumin; Zhao, Min; Lu, Xiang; Lu, Juan; Ji, Likai; Shen, Quan; Wang, Xiaochun; Yang, Shixing; Zhang, Wen
Abstract: Emerging and existing viruses from various human and animal samples have been studied and analyzed using viral metagenomics, which has proven to be an effective technique. Foxes, as a kind of significant economic animal, are widely raised in China. Viruses carried by foxes may potentially infect humans or other animals. There are currently very few studies of faecal virome in farmed foxes. Using viral metagenomics, we evaluated the faecal virome of twenty-four foxes collected from the same farm in Jilin Province, China. Some sequences more closely related to the families Parvoviridae, Picornaviridae, Smacoviridae, Anelloviridae, and Herpesviridae were detected in the faecal sample. The main animal viruses that infect farmed red foxes were parvovirus and picornavirus. Five smacovirus strains were found and provided evidence for genetic diversity in the genus Smacoviridae . In addition, some viruses infecting avian species or rats were detected in this study. The study helped us better understand faecal virome in farmed red foxes and assisted in the surveillance and prevention of viral diseases in these animals.